ICT development of community in rural areas - Kamarudin, Syafila; Omar, Siti Zobidah; Bolong, Jusang; Osman, Mohd Nizam; Mahamed, Mastura (Human Resource Management Academic Research Society, 2019)
Information Communication Technology (ICT) is no longer limited to urban population, but it has become increasingly relevant to the rural population. The use of ICT is evident through availability of ICT services for all in Malaysia’s rural areas. The internet in particular is gaining influences in the lives of rural communities in many aspects such as socially, educationally or economically is moving towards digitization. The establishment of ICT centers in rural areas has accelerated the adaptation of ICT in rural areas. Therefore, in general, this article will discuss the importance of ICT usage for rural community, and the government initiatives toward enhancing the ICT usage especially in the telecentre. The significance of having telecentres function as the centre for ICT excellence in rural areas. The telecentre provides ICT facilities such as internet and computer training room for use by rural community. Moreover, the establishment of telecentre is aiming for ICT awareness among the rural; one of the government initiatives.